A critical evaluation of the curriculum development strategy of the LIS education programs in Sri Lanka - Wijetunge, Pradeepa (Emerald Inc., 2009)
Purpose: A comprehensive analysis of the LIS education system was carried out covering the 2004-2007 period and it was established that currently 24 LIS education programs are conducted in Sri Lanka by eight educational institutions. This paper presents a critical evaluation of the curriculum development strategy of the LIS education programs in Sri Lanka based on the major research